Exploring the effect of polyfluorene copolymerisation for improved material design - Lambeva, NT (2020)
The discovery of electroluminescence from conjugated polymers was followed by tremendous academic and commercial interest in the field of polymer optoelectronics. Conjugated polymer materials have been shown to possess beneficial qualities for device fabrication such as low-cost, large area manufacturing and the potential for realizing flexible applications. Polyfluorenes, in particular, are a class of conjugated polymers which have been realized in a number of applications such as organic light emitting diodes, solar cells and field-effect transistors. The widespread commercialization of such products critically depends on improving device efficiencies. This can be accomplished by both advancing device engineering and improving material design. For the realization of the latter, fundamental understanding of the interplay between material chemistry and physics is required. This motivated the work in this thesis which is concerned with the structure-property relationship in polyfluorene containing copolymers. The well studied polyfluorene poly(9,9-dioctylfluorene) (PFO) was selected as the model polymer due to its complex phase morphology which allowed to additionally investigate the effect of film microstructure on the photophysics of the copolymers. The optoelectronic properties of PFO can be varied by the copolymerisation of suitable comonomers giving valuable insight into the relationship between chemical structure and photophysical properties that can guide future material design for device applications.